2016
DOI: 10.1155/2016/9058686
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Growth Mechanism of Nickel Nanowires Resulting from Reduction of Nickel Formate in Polyol Medium

Abstract: Nickel linear nanostructures were synthesized by reduction of nickel formate with hydrazine hydrate in ethylene glycol medium in the absence of any surfactants or capping agents for direction of the particles growth. The effect of the synthesis conditions such as temperature, reduction time, type of polyol, and nickel formate concentration on the reduction products was studied. The size and morphology of the nickel nanowires were characterized by X-ray diffraction, scanning, and transmission electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In 2016, Xia and Wen optimized the large-scale synthesis conditions of h-NiNWs and found that the size and morphology of NiNWs can be tailored by adjusting the reaction temperature, time length, and surfactant concentration . Logutenko et al also made a similar observation wherein a decrease in the nickel precursor concentration resulted in a decrease in diameters of the nanowires …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2016, Xia and Wen optimized the large-scale synthesis conditions of h-NiNWs and found that the size and morphology of NiNWs can be tailored by adjusting the reaction temperature, time length, and surfactant concentration . Logutenko et al also made a similar observation wherein a decrease in the nickel precursor concentration resulted in a decrease in diameters of the nanowires …”
Section: Introductionmentioning
confidence: 97%
“…44 Logutenko et al also made a similar observation wherein a decrease in the nickel precursor concentration resulted in a decrease in diameters of the nanowires. 45…”
Section: Introductionmentioning
confidence: 99%
“…From previous studies, the nanowire form of the nanoparticles is attributed to the crystallite growth controlled by temperature and templating conditions. The pyrolytic condition of the carbon-rich material in the pyrolytic system may be attributed as influencing the aggregation of Ni NPs [ 25 , 26 ]. This is confirmed by the EDX analysis results presented in Table 1 , suggesting an Ni amount of about 31.67 wt.% in Ni/BC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the PVP additive concurrently acts as the structure‐directing agent, protective agent, and stabilizer, and the O and N atoms in it can provide lone electron pairs to Ni 2+ , which further forms a coordination complex and reducing the concentration of free Ni 2+ . [ 11 ] During the whole reaction process, the external magnetic field acts as a key factor for inducing the formation of nanowires, which promotes the directional growth of the nascent nickel nuclei along the direction of the magnetic field ( Figure a).…”
Section: Resultsmentioning
confidence: 99%